Subepidermal calcified nodule in upper eyelid: A case report and review of the literature - Samaka, Rehab Monir (Oman J Ophthalmol, 2015)
Calcinosis cutis involves the inappropriate deposition of calcium within the dermis layer of the skin and is often associated with autoimmune diseases. A 3-year-old healthy Omani child presented for evaluation of asymptomatic hard nodule on the left upper eyelid. Pathological examination identified the mass as subepidermal calcified nodule. The patient had no history of trauma or metabolic disturbances. Serum levels of calcium and phosphate were normal. Idiopathic calcinosis cutis should be included in the differential diagnosis for eye lid mass.